2020
DOI: 10.1002/acr.24064
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation Rates for Physical Therapy, Lifestyle Counseling, and Pain Medications for Managing Knee Osteoarthritis in Ambulatory Care Settings: A Cross‐Sectional Analysis of the National Ambulatory Care Survey (2007–2015)

Abstract: Objective. To describe and compare triennial rates of physicians' recommendations for physical therapy (PT), lifestyle counseling, and pain medication for knee osteoarthritis (OA) and to identify patient, physician, and practice factors associated with each treatment recommendation.Methods. We conducted a cross-sectional analysis examining data between 2007 and 2015 from the National Ambulatory Medical Care Survey. Visits to orthopedists and primary care physicians for knee OA were identified and assessed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…However, only 9.4% of those surveyed reported that exercise program was recommended as a treatment in our study. These findings are consistent with previous reports on low-rate recommendation of exercise, noncompliance to exercise therapy and lifestyle counseling, and warrant further investigation to increase this low level of adherence [31,32]. The most appropriate knee OA management, including exercise therapy, should be designed according to a patient-centered approach.…”
Section: Discussionsupporting
confidence: 88%
“…However, only 9.4% of those surveyed reported that exercise program was recommended as a treatment in our study. These findings are consistent with previous reports on low-rate recommendation of exercise, noncompliance to exercise therapy and lifestyle counseling, and warrant further investigation to increase this low level of adherence [31,32]. The most appropriate knee OA management, including exercise therapy, should be designed according to a patient-centered approach.…”
Section: Discussionsupporting
confidence: 88%
“… 5 ) Pain control is important when performing exercise, and it was revealed that about half of the patients receiving physical therapy used non-steroidal anti-inflammatory drugs (NSAIDs). 6 ) Topical NSAIDs are the most strongly recommended treatment modality according to the latest Osteoarthritis Research Society International (OARSI) guidelines, whereas oral NSAIDs are conditionally recommended. 5 )…”
Section: Introductionmentioning
confidence: 99%
“…Our findings were consistent with other published studies that a lack of referral results in underutilization of OA health services. (Cottrell, Roddy, & Foster, 2010;Hagglund, Clark, Hilton, & Hewett, 2005) Recommendation rates for PT for knee OA by physicians have declined by nearly 50% from 2007 to 2015 (Khoja, Almeida, & Freburger, 2019), which is concerning given our study's findings highlighting the importance of physician referrals and evidence for nonsurgical knee OA treatments (Hochberg et al, 2012). Further research is needed to develop and implement practical strategies to improve physician referral patterns to PT for knee OA.…”
Section: Discussionmentioning
confidence: 78%